Voluntary Public Unemployment Insurance - Donald O. Parsons; Torben Tranæs; Helene Bie Lilleør (Center for Economic Studies and ifo Institute (CESifo), 2015)
Denmark has drawn much attention for its active labor market policies, but is almost unique in offering a voluntary public unemployment insurance program requiring a significant premium payment. A safety net program–a less generous, means-tested social assistance plancompletes the system. The voluntary system emerged as one of many European Ghent systems, essentially government subsidized trade union plans, but has since lost many key features of such plans. We assess system performance using a 10% sample of the Danish population drawn from administrative data. Coverage rates for the voluntary programs are surprisingly high, approximately 80 percent of the workforce, but the program has predictable selection effects, including adverse selection across risk classes and a substantial charity hazard (low coverage among those with generous treatment under the safety net program). The latter appears to explain the difficulty of shifting to a compulsory system; redistribution effects would be concentrated among the previously uninsured in the lowest decile of the income distribution, a problem in the Danish welfare state.
Keywords: J65; H40; 330; unemployment insurance; social assistance; unemployment